The digitalised image of God: artificial intelligence, liturgy, and ethics - Xu, Ximian (Routledge science and religion series, 2025)
This book focuses on the idea of the imago Dei to engage theologically with artificial intelligence (AI). It reflects on how enormous progress in the development of AI has raised some challenges to Christian theology